Fault detection in coal fired power plants using nonlinear filtering - Korbicz, Józef (1951- ); Fathi, Zohreh; Ramirez, W. Fred (Zielona Góra: Uniwersytet Zielonogórski)
On the contrary to many recent attempts using knowledge-based system techniques where diagnostic analysis is based solely on measurable and observable data, in this work we propose to investigate the adaptive inclusion of a state and/or parameter estimation module in the diagnostic reasoning loop, in addition to employing information based on measurable data.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka